A Review and Typology of Circular Economy Business Model Patterns - Lüdeke‐Freund, Florian; Gold, Stefan; Bocken, Nancy M. P. (Journal of industrial ecology, 2019)
Summary The circular economy (CE) requires companies to rethink their supply chains and business models. Several frameworks found in the academic and practitioner literature propose circular economy business models (CEBMs) to redefine how companies create value while adhering to CE principles. A review of these frameworks shows that some models are frequently discussed, some are framework specific, and some use a different wording to refer to similar CEBMs, pointing to the need to consolidate the current state of the art. We conduct a morphological analysis of 26 current CEBMs from the literature, which includes defining their major business model dimensions and identifying the specific characteristics of these dimensions. Based on this analysis, we identify a broad range of business model design options and propose six major CEBM patterns with the potential to support the closing of resource flows: repair and maintenance; reuse and redistribution; refurbishment and remanufacturing; recycling; cascading and repurposing; and organic feedstock business model patterns. We also discuss different design strategies to support the development of these CEBMs.